On predicting the length, width, and volume of the jet diffusion flame. (5th February 2016) - Kang, Yinhu; Lu, Tianfeng; Lu, Xiaofeng; Gou, Xiaolong; Huang, Xiaomei; Peng, Shini; Ji, Xuanyu; Zhou, Yang; Song, Yangfan
Highlights: Flow, mixing, length and width behaviors of jet flames are theoretically studied. New forms of correlations for length, width, and volume of jet flames are proposed. Length, width, and volume correlations of the DME jet diffusion flames are developed. The current correlations have higher accuracy for the jet diffusion flames. Graphical Abstract: Abstract: In this paper, the flame length ( Lf ), width ( Wf ), and volume ( Vf ) behaviors of the jet diffusion flame were experimentally and theoretically studied. Various fuel nozzle diameters ( df ), fuel jet velocities ( uf ), and air co-flow velocities ( uco ) were involved in the experiments to investigate their impacts on flame characteristics systematically. Additionally, the analytical solutions for the flow field, fuel concentration, Lf, Wf, and Vf of the jet diffusion flame were derived by theoretical analysis. The results show that flame shape and dimensions of the jet diffusion flame depended on fuel jet Reynolds number ( Ref ) inherently. At the laminar regime, the dimensionless flame length normalized by df ( Lf * ) was proportional to Ref . At the laminar–turbulent transitional regime and fully-turbulent regime, Lf * kept nearly constant. The dimensionless flame width ( Wf * ) remained basically unchanged at the laminar or fully-turbulent regime; but it increased fairly quickly with the increment in Ref at the laminar–turbulent transitional regime. The dimensionless flame volume ( Vf * ) increased linearly with Ref at the laminar regime, and parabolically with Ref at the laminar–turbulent transitional regime. At the fully-turbulent regime, Vf * kept constant. Besides, with the increase in uco, Lf * maintained nearly unchanged, and Wf * decreased exponentially. Based on the above behaviors, new forms of correlations for Lf *, Wf *, and Vf * of the jet diffusion flame were proposed presently. Comparisons of these correlations with the existing ones in the literature were also conducted in this paper. Moreover, Lf *, Wf *, and Vf * correlations for the dimethyl ether/air jet diffusion flames were developed herein.